FAKTOR YANG BERHUBUNGAN DENGAN KONSUMSI FAST FOOD PADA MURID SMA BUDHI WARMAN 1 JAKARTA TIMUR - Mardiyah, Sarah; Shabrina, Nurul (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
Fast Food is a type of practical food that contains high levels of fat, sodium, sugar, and energy. However, it’s low in vitamins and fiber. The aim of research is to determine the factors associated with fast food consumption among students at SMA Budhi Warman 1 East Jakarta in 2023. The research location at Budhi Warman 1 High School, East Jakarta. The research time in August 2023. This research is a quantitative study with a cross sectional research design. The research population is 180 students with a total sample of 137 samples. The sampling technique uses stratified random sampling. Sources and types of primary and secondary data. Data analysis used univariate and bivariate with the chi square test. Univariate results: frequent fast food frequency 65%, lack of nutritional knowledge 62,8%, peer influence 62,8%, negative attitude 70,1%. Meanwhile, the bivariate results showed that there was a relationship between nutritional knowledge, peer influence, and attitudes towards fast food consumption (p value <0,001). This research recommends that can better understand about snacks and healthy foods that are good for consumption.